Analisis Pengujian Database SQL dan NoSQL pada Aplikasi Berbasis Microservice dengan Spring Boot - Fatich, Steven Arycena; Susetyo, Yeremia Alfa (Kesatria : Jurnal Penerapan Sistem Informasi (Komputer dan Manajemen), 2025)
Efficient database utilization is essential in application development. This study aims to analyze the performance of PostgreSQL (SQL) and MongoDB (NoSQL) in CRUD operations and data aggregation using the Spring Boot framework. The research stages include developing a test application, conducting 10 simulation tests for each operation, and analyzing response times. The results indicate that MongoDB excels in create operations with an average response time of 230.4 ms and delete operations at 2.6 ms. In contrast, PostgreSQL demonstrates better efficiency in read operations and aggregations (sum, average, min, max) with superior response times